PENGARUH KUALITAS MAKANAN, KUALITAS LAYANAN DAN LINGKUNGAN FISIK TERHADAP KEPUASAN DAN BEHAVIORAL INTENTIONS ( STUDI DI MÉTIS RESTAURANT ) - Evirasanti, Meitha; Rahyuda, Ketut; Kerti Yasa, Ni Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.12.TAHUN 2016, 2016)
The purpose of this study were to describe and analyze the influence of the quality of food, quality of service and the physical environment on satisfaction and behavioral intentions. The study was conducted in Métis Restaurant, using 150 visitors as sample. Methods of data collection using questionnaires, in which data is analyzed using Structural Equation Model (SEM). Results from this study indicate that quality of food, quality of service and physical environment has a positive and significant direct influence, both for customer satisfaction and behavioral intentions. Satisfaction also has positive and significant effect on behavioral intentions directly.The implication of this study, that the three aspects of dining experiences were able to achieve satisfaction and in the end would create behavioral intentions. The restaurant was suggested to to improve the dinning experience aspects, such as menu variety, friendliness and the lightning level.
Keywords: Kualitas Makanan, Kualitas Layanan, Lingkungan Fisik, Kepuasan, Behavioral Intentions